Development of a Validated HPTLC Method for Quantification of Scopoletin in Ipomoea Turpethum Root and its Market Formulations - Modi, Karuna P.; Pagi, Kashmir B.; Lahiri, Suman K.; Shah, Mamta B. (Indian Journal of Natural Products, 2019)
Background: Ipomoea turpethum R. Br.(F: Convolvulaceae)commonly known as Indian Jalap in English and Nisoth in Hindi has been commonly used as a purgative. In India under the name of Nisoth two drugs are available commercially, Marsdeniatenacissima as white Nisoth and Ipomoea turpethum as black Nisoth. The presence of a coumarin, scopoletin in I. turpethum distinguishes the two drugs available under the name of Nisoth. Purpose: This paper is aimed to present a simple method of identification and quantification of scopoletin in I. turpethum and to check the presence of same in its different market formulations like Anand Churna (F-1), KayamChurna (F-2), Bhavnagari Churna (F-3), Manjistadi Churna (F-4), Abhayadi Modak (F-5) using HPTLC. Study design: Simple and accurate HPTLC method is developed using scopoletin as a marker for chemo-profiling of I. turpethum and using it for evaluation of market formulations. Methods: The chromatographic method for scopoletin was developed using silica gel 60 F plates as stationary phase and toluene: ether (1: 1) with 10% glacial 254 acetic acid as a mobile phase. The method was validated in terms of accuracy, precision, specificity, linearity, limit of detection (3:1) and limit of quantification (10:1). Results: The chromatographic method gave good resolution of scopoletin, without any interference with the other compounds present in I. turpethum and its formulations. It was noted that amongst all the spots scopoletin resolved at R 0.27, exhibiting characteristic blue fluorescence under UV light in I. turpethum f andits different market formulations when scanned at 366 nm. Scopoletin content in I. turpethum root and its formulations was found to be equivalent. Among all formulations, the formulation F-5 (vati) contained less amount of scopoletin when compared to the actual amount of the I. turpethum incorporated. Thus, it may be concluded that in F-5 being vati, presence of excipients and method of preparation might have influenced the scopoletin content. Conclusion: The method is simple, sensitive and precise. It can be used for the routine quality control testing of I. turpethum and to check presence of it in its different market formulations.
Keywords: HPTLC; Ipomoea turpethum root; market formulations; scopoletin